Tunable surface plasmon-polariton resonance in organic light-emitting devices based on corrugated alloy electrodes - Xue-Mei Wen (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
We report a feasible method to realize tunable surface plasmon-polariton (SPP) resonance in organic light-emitting devices (OLEDs) by employing corrugated Ag-Al alloy electrodes. The excited SPP resonance induced by the periodic corrugations can be precisely tuned based on the composition ratios of the Ag-Al alloy electrodes. With an appropriate composition ratio of the corrugated alloy electrode, the photons trapped in SPP modes are recovered and extracted effectively. The 25% increasement in luminance and 21% enhancement in current efficiency have been achieved by using the corrugated Ag-Al alloy electrodes in OLEDs.